High glucose stimulates expression of aldosterone synthase (CYP11B2) and secretion of aldosterone in human adrenal cells - Hiroki Shimada; Naotaka Kogure; Erika Noro; Masataka Kudo; Kaori Sugawara; Ikuko Sato; Kyoko Shimizu; Makoto Kobayashi; Dai Suzuki; Rehana Parvin; Takako Saito‐Ito; Akira Uruno; et al. (FEBS Open Bio, 2017)
Aldosterone synthase is the key rate‐limiting enzyme in adrenal aldosterone production, and induction of its gene (CYP11B2) results in the progression of hypertension. As hypertension is a frequent complication among patients with diabetes, we set out to elucidate the link between diabetes mellitus and hypertension. We examined the effects of high glucose on CYP11B2 expression and aldosterone production using human adrenal H295R cells and a stable H295R cell line expressing a CYP11B2 5′‐flanking region/luciferase cDNA chimeric construct. d‐glucose (d‐glu), but not its enantiomer l‐glucose, dose dependently induced CYP11B2 transcription and mRNA expression. A high concentration (450 mg·dL−1) of d‐glu time dependently induced CYP11B2 transcription and mRNA expression. Moreover, high glucose stimulated secretion of aldosterone into the media. Transient transfection studies using deletion mutants/nerve growth factor‐induced clone B (NGFIB) response element 1 (NBRE‐1) point mutant of CYP11B2 5′‐flanking region revealed that the NBRE‐1 element, known to be activated by transcription factors NGFIB and NURR1, was responsible for the high glucose‐mediated effect. High glucose also induced the mRNA expression of these transcription factors, especially that of NURR1, but NURR1 knockdown using its siRNA did not affect high glucose‐induced CYP11B2 mRNA expression. Taken together, it is speculated that high glucose may induce CYP11B2 transcription via the NBRE‐1 element in its 5′‐flanking region, resulting in the increase in aldosterone production although high glucose‐induced NURR1 is not directly involved in the effect. Additionally, glucose metabolism and calcium channels were found to be involved in the high glucose effect. Our observations suggest one possible explanation for the high incidence of hypertension in patients with diabetes.